Enhanced Cross-Shelf Exchange Between the Pacific Ocean and the Bungo Channel, Japan Related to a Heavy Rain Event - Morimoto, Akihiko; Dong, Menghong; Kameda, Mahiro; Shibakawa, Taiga; Hirai, Makiko; Takejiri, Kouhei; Guo, Xinyu; Takeoka, Hidetaka (Frontiers in Marine Science, 2022)
A heavy rain event occurred in early July 2018 near the Seto Inland Sea. Despite clear weather after the heavy rain, the water temperature at 5 m depth on the eastern coast of the Bungo Channel decreased by approximately 3°C. Postulating that the water temperature decrease was related to the heavy rain event, we analyzed observed data during and after the heavy rain and conducted numerical experiments. We found that the surface water temperature decrease was caused by vertical mixing of cold water supplied from the Pacific Ocean in the bottom layer. Numerical experiments revealed that the bottom cold water from the Pacific Ocean was not controlled by the heavy rain event but was intensified by the heavy rain event. The lower salinity (lower water density) due to the heavy rain lasted until the end of August. This lower density intensified the gravitational circulation in the Bungo Channel for 2 months, which led to a 17.5% increase in inflow from the Pacific Ocean in the bottom layer and a 20% increase in the dissolved inorganic nitrogen flux to the Bungo Channel.